Frequency Specific Modulation of Human Somatosensory Cortex - Feurra, Matteo; Paulus, Walter; Walsh, Vincent; Kanai, Ryota (Frontiers in Psychology, 2011)
Oscillatory neuronal activities are commonly observed in response to sensory stimulation. However, their functional roles are still the subject of debate. One-way to probe the roles of oscillatory neural activities is to deliver alternating current to the cortex at biologically relevant frequencies and examine whether such stimulation influences perception and cognition. In this study, we tested whether transcranial alternating current stimulation (tACS) over the primary somatosensory cortex (SI) could elicit tactile sensations in humans in a frequency-dependent manner. We tested the effectiveness of tACS over SI at frequency bands ranging from 2 to 70 Hz. Our results show that stimulation in alpha (10–14 Hz) and high gamma (52–70 Hz) frequency range produces a tactile sensation in the contralateral hand. A weaker effect was also observed for beta (16–20 Hz) stimulation. These findings highlight the frequency dependency of effective tACS over SI with the effective frequencies corresponding to those observed in previous electroencephalography/magnetoencephalography studies of tactile perception. Our present study suggests that tACS could be used as a powerful online stimulation technique to reveal the causal roles of oscillatory brain activities.